Carbon Dioxide Reduction with Hydrogen on Carbon‐Nanotube‐Supported Catalysts under Supercritical Conditions. Issue 9 (3rd June 2019) - Bogdan, Victor I.; Pokusaeva, Yana A.; Koklin, Alexey E.; Savilov, Sergei V.; Chernyak, Sergei A.; Lunin, Valery V.; Kustov, Leonid M.
Abstract : Reduction of CO2 with hydrogen into CH4 is studied for the first time on carbon‐nanotube‐supported Co and Ni catalysts under supercritical conditions. The extremely high selectivity toward methanation close to 100% is found with a quite good stability of the catalytic activity. Abstract : The most practical way of CO2 utilization is its hydrogenation into valuable products. Reduction of CO2 with hydrogen into CH4 is studied for the first time under supercritical conditions on Co and Ni nanoparticles supported onto carbon nanotubes. The extremely high selectivity toward methanation close to 100% is found with a high stability of the catalytic activity.